Enhanced strength-ductility synergy in a wire and arc additively manufactured Mg alloy via tuning interlayer dwell time - Dong Ma; Chunjie Xu; Shang Sui; Jun Tian; Can Guo; Xiangquan Wu; Zhongming Zhang; Dan Shechtman; Sergei Remennik (Journal of Magnesium and Alloys, 2023)
Strength-ductility trade-off is a common issue in Mg alloys. This work proposed that a synergistic enhancement of strength and ductility could be achieved through tuning interlayer dwell time (IDT) in the wire and arc additive manufacturing (WAAM) process of Mg alloy. The thermal couples were used to monitor the thermal history during the WAAM process. Additionally, the effect of different IDTs on the microstructure characteristics and resultant mechanical properties of WAAM-processed Mg alloy thin-wall were investigated. The results showed that the stable temperature of the thin-wall component could reach 290 °C at IDT=0s, indicating that the thermal accumulation effect was remarkable. Consequently, unimodal coarse grains with an average size of 39.6 µm were generated, and the resultant room-temperature tensile property was poor. With the IDT extended to 60s, the thermal input and thermal dissipation reached a balance, and the stable temperature was only 170 °C, closing to the initial temperature of the substrate. A refined grain structure with bimodal size distribution was obtained. The remelting zone had fine grains with the size of 15.2 µm, while the arc zone owned coarse grains with the size of 24.5 µm. The alternatively distributed coarse and fine grains lead to the elimination of strength-ductility trade-off. The ultimate tensile strength and elongation of the samples at IDT=60s are increased by 20.6 and 75.0% of those samples at IDT=0s, respectively. The findings will facilitate the development of additive manufacturing processes for advanced Mg alloys.